Investigating students preception of gamification on vocabulary learning using Marbel - Ichi Ahada (Universitas PGRI Madiun, 2021)
It is critical to know and memorize the vocabulary of a foreign language if one wishes to learn it, and repetition is necessary to aid in the retention of new knowledge. This paper investigated primary school students’ perception of gamification on vocabulary learning with 32 participants divided into two groups: Primary 1 and Primary 2. The research purpose on perception using Marbel for primary students and conducted with quantitative method. The results of this research show that gamification can improve students’ vocabulary size with majority of students’ feedback saying that they preferred Marbel than worksheet to learn vocabulary. At the same time, students were learning through their failures throughout the gameplay, they were encouraged to memorize the words. This will help students grow into independent and competent learners.